2020
DOI: 10.14202/vetworld.2020.731-738
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial remodeling in dogs with mitral valve endocardiosis

Abstract: Background and Aim: Left ventricular myocardial remodeling could play an important role in the progression of chronic heart failure (CHF) syndrome in dogs with mitral valve endocardiosis. The aim of this study was to evaluate the left ventricular myocardial remodeling in dogs with mitral valve endocardiosis and to study the dependence of the incidence of this pathological phenomenon on the functional class (FC) of progression of the CHF syndrome. Materials and Methods: A total of 108 afflicted dogs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…The distribution of parietal stress can be deduced from myocardial thickness patterns [ 4 ]. One hypothesis to be considered based on the results obtained is that the ventral wall in its portion of the basal segment is exposed to greater stresses due to the effect of gravity, since dogs are quadrupedal animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of parietal stress can be deduced from myocardial thickness patterns [ 4 ]. One hypothesis to be considered based on the results obtained is that the ventral wall in its portion of the basal segment is exposed to greater stresses due to the effect of gravity, since dogs are quadrupedal animals.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular remodeling is the result of a combination of biochemical, physical, structural, molecular and geometric factors. Given that the left ventricular cavity loses its ellipsoid shape, tending to sphericity, functionality is impaired by increased parietal stress, increased oxygen consumption, subendocardial hypoperfusion and sustainment of neurohormonal and mechanical mechanisms [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cardiac remodeling responds to many pathological factors [36][37][38]. Volume overload can cause cardiac wall stress and can alter myocardial oxygen demand, increasing oxidative stress levels [38,39]. Moreover, previous studies in dogs have demonstrated the relationship between cardiac disease-induced cardiac remodeling and increased oxidative stress [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Pathology of small domestic animals with inflammatory and immune development mechanism is an urgent problem of veterinary medicine [1][2][3]. One of such diseases of cats is acute bacterial cholangiohepatitis [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%